(untitled) (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: The present study analyzed the seminal plasma proteome and possible relationships between proteins and semen quality in azoospermic and normal Simmental bulls. Materials and Methods: Fresh semen plasma samples from the Lembang Artificial Insemination Center were used for this study, including one bull (76´ ejaculate) with very poor semen quality/ azoospermia (poor fresh semen/infertile; PFS) and three bulls with normal semen quality (normal fresh semen; NFS) for proteomic analysis using a pooled system (NFS-Stud) (60´ ejaculate). The only males obtained with very low quality or azoospermia (PFS) had sperm motility of <10% (one head). Bulls with azoospermic conditions produce fresh semen without sperm or with very little sperm concentration. A total of 109 proteins were identified in the seminal plasma of Simmental bulls analyzed using liquid chromatography-mass spectrometry. Bioinformatics analysis was used to explore total protein, expression, function, and protein mechanism in the seminal plasma of Simmental bulls. Results: The results showed that the seminal plasma proteins expressed in NFS bulls include ELSPBP1, SIL1, HSPA13, angiotensin-1 covering enzyme, and CRISP1. On the other hand, B2M, C3, CFB, venin-2, and cathepsin S contribute significantly to PFS. The NFS bull proteins play important roles in sperm capacitation, protein transport, sperm motility, spermatogenesis, immune tolerance, and fertilization, while the PFS proteins perform apoptotic and antigen pathway functions. Conclusion: There is an interaction between proteins in the seminal plasma of males with poor semen quality (PFS) and cases of infertility (azoospermia) that cause a decrease in sperm quality in PFS bulls. J. Adv. Vet. Anim. Res., 10(3): 370–377, September 2023 http://doi.org/10.5455/javar.2023.j689